A New Phenolic Constituent and a Cyanogenic Glycoside from Balanophora involucrata (Balanophoraceae). Issue 6 (18th June 2013) - She, Gai‐Mei; Zhang, Ying‐Jun; Yang, Chong‐Ren
Abstract Balanophora involucrata Hook.f. & Thomson (Balanophoraceae) is a parasite plant often growing on the roots of leguminous plants. The whole herb has been used medicinally for the treatment of irregular menstruation, cough, hemoptysis, traumatic injury and bleeding, dizziness and gastralgia in Yunnan Province, China. The 2, 2‐diphenyl‐2‐picrylhydrazyl (DPPH) assay on the 60% aq. acetone extract of the fresh whole plant of B. involucrata showed considerable radical‐scavenging activity (SC50 15.3 μg/ml). Further purification on the extract led to the isolation of one new phenolic glycoside, sieboldin‐3′‐ketocarboxylic acid (1), and one new cyanogenic glycoside, proacacipetalin 6′‐O‐β‐D‐glucopyranoside (2), together with 26 known compounds including three 4″‐O‐galloyl and 2″, 3″‐O‐(S)‐hexahydroxydiphenoyl (HHDP) derivatives of dihydrochalcone glucosides, seven hydrolyzable tannins, and alkane glycosides. The cyanogenic compound isolated from the Balanophoraceae family for the first time might be a signal molecule between B. involucrata and its hosts. The free‐radical‐scavenging activity of the isolated compounds was also examined by DPPH assay.